2019
DOI: 10.1038/s41419-019-1987-1
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Wnt/β-catenin pathway leads to dysfunction of intestinal regeneration during necrotizing enterocolitis

Abstract: Necrotizing enterocolitis (NEC) is a devastating neonatal disease characterized by acute intestinal injury. Intestinal stem cell (ISC) renewal is required for gut regeneration in response to acute injury. The Wnt/β-catenin pathway is essential for intestinal renewal and ISC maintenance. We found that ISC expression, Wnt activity and intestinal regeneration were all decreased in both mice with experimental NEC and in infants with acute active NEC. Moreover, intestinal organoids derived from NEC-injured intestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 48 publications
7
54
0
1
Order By: Relevance
“…Experimental pups undergoing NEC induction (number for each study reported below) were separated from their mothers, while controls remained with mothers to breastfeed ( n = 10). NEC was induced in neonatal C57BL/6 mixed sex mice from postnatal day 5–9 by gavage feeding of hyperosmolar formula, exposure to hypoxia and oral LPS injection (day 6 and 7, 4 mg/kg) for 4 days 7 . At postnatal day 9, pups were sacrificed, and the ileum was harvested for further studies.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental pups undergoing NEC induction (number for each study reported below) were separated from their mothers, while controls remained with mothers to breastfeed ( n = 10). NEC was induced in neonatal C57BL/6 mixed sex mice from postnatal day 5–9 by gavage feeding of hyperosmolar formula, exposure to hypoxia and oral LPS injection (day 6 and 7, 4 mg/kg) for 4 days 7 . At postnatal day 9, pups were sacrificed, and the ileum was harvested for further studies.…”
Section: Methodsmentioning
confidence: 99%
“…Murine small intestine-derived organoids were cultured according to a previous publication 7 . Briefly, small intestine was harvested from neonatal C57BL/6 mice and cut into small segments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, it is important to remember that Paneth cell loss may also impact the stem cell niche. A healthy stem cell cohort is critical to induce epithelial restitution following injury as Paneth cells support the stem cell niche through the production of EGF, Notch, and Wnt (27,88,104,138).…”
Section: Paneth Cells and Necrotizing Enterocolitis (Nec)mentioning
confidence: 99%
“…It is now well established that intestinal crypt cells respond to damage induced by high-dose irradiation or chemicals by activation of reserve stem cells 5,[25][26][27] . Here, we reveal intestinal crypt cells exhibit a novel response to a diarrheal virus (Fig.…”
Section: Discussionmentioning
confidence: 99%